2018
DOI: 10.1248/yakushi.17-00194
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Time-to-onset of Interstitial Lung Disease after the Administration of Small Molecule Molecularly-targeted Drugs

Abstract: The aim of this study was to investigate the time-to-onset of drug-induced interstitial lung disease (DILD) following the administration of small molecule molecularly-targeted drugs via the use of the spontaneous adverse reaction reporting system of the Japanese Adverse Drug Event Report database. DILD datasets for afatinib, alectinib, bortezomib, crizotinib, dasatinib, erlotinib, everolimus, geˆtinib, imatinib, lapatinib, nilotinib, osimertinib, sorafenib, sunitinib, temsirolimus, and tofacitinib were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…21 Another report indicated that the median onset time of drug-induced ILD for crizotinib was within 1 month in the study via the use of the spontaneous adverse reaction reporting system of the Japanese Adverse Drug Event Report database. 32 Median time to onset of ILD for EGFR-TKI gefitinib was reported to be 24 days in Japanese patients, which was similar to those undergoing crizotinib therapy. 33 Overall, under crizotinib administration, there is a trend of early ILD onset.…”
Section: Discussionmentioning
confidence: 76%
“…21 Another report indicated that the median onset time of drug-induced ILD for crizotinib was within 1 month in the study via the use of the spontaneous adverse reaction reporting system of the Japanese Adverse Drug Event Report database. 32 Median time to onset of ILD for EGFR-TKI gefitinib was reported to be 24 days in Japanese patients, which was similar to those undergoing crizotinib therapy. 33 Overall, under crizotinib administration, there is a trend of early ILD onset.…”
Section: Discussionmentioning
confidence: 76%
“…The median time-to-onset and onset-pattern of the DILD after administration of monoclonal antibody agents in this study, and small molecule molecularlytargeted drugs in our previous study with the same mechanism of action, were compared. 37) The median time-to-onset of DILD for the monoclonal antibodies of EGFR, cetuximab (42 d) and panitumumab (49 d), showed that these occurred later than those observed for the small molecule molecularly-targeted drugs of the EGFR TKIs, erlotinib (21 d), geˆtinib (24 d), and osimertinib (34.5 d). In addition, the DILD onset time proˆles for cetuximab and panitumumab were estimated to be the random failure type.…”
Section: Discussionmentioning
confidence: 94%
“…35,36) Our previous study demonstrated that the median time-to-onset of DILD for small molecule molecularly-targeted drugs such as dasatinib, erlotinib, everolimus, geˆtinib, lapatinib, osimertinib, and temsirolimus ranged from 1 to 2 months. 37) In addition, the median time-to-onset of the DILD for alectinib, imatinib, and tofacitinib ranged from 2 to 3 months, while the median time-to-onset of the DILD for sunitinib and sorafenib ranged from 8 to 9 months. The Weibull distributions for bortezomib, crizotinib, erlotinib, afatinib, geˆtinib, dasatinib, nilotinib, lapatinib, imatinib, and sorafenib were estimated toˆt the early failure type proˆle, while those for osimertinib and everolimus were estimated toˆt the wear out failure type proˆle.…”
Section: Introductionmentioning
confidence: 97%
“…The result of the mining algorithm for DIILD was a set of 11 rules, respectively ( Table 2). {sho-saikoto, 50-59 years}, {sho-saiko-to, 60-69 years}, {sho-saiko-to, 70-79 years} ⇒ {DIILD}, {sho-saiko-to-ka-kikyo-sekko, 70-79 years} ⇒ {DIILD} demonstrated high lift scores ( Table 2, id (8)(9)(10)(11) and…”
Section: Resultsmentioning
confidence: 99%